20-Hydroxyecdysone regulates the transcription of the lysozyme via Broad-Complex Z2 gene in silkworm, Bombyx mori. (May 2019) - Ma, Hanxiu; Abbas, Muhammad Nadeem; Zhang, Kui; Hu, Xiaosong; Xu, Man; Liang, Hanghua; Kausar, Saima; Yang, Liqun; Cui, Hongjuan
Abstract: Broad-Complex Z2 (Br-C Z2) is an ecdysone inducible transcription factor that regulates physiological, innate immune and developmental events in insects. Here, we identified an orthologue of Br-C Z2 from silkworm, Bombyx mori ( BmBr-C Z2 ) to study its involvement in immune responses. The quantitative real-time PCR analysis revealed that BmBr-C Z2 was expressed ubiquitously in all tested tissues under normal physiological conditions. Further, developmental profile displayed that BmBr-C Z2 expression was detectable in different developmental stages, however the gene's expression was highest in the molting and pre-pupal stages. Administration of 20-hydroxyecdysone (20E) enhanced the expression levels of BmBr-C Z2 in hemocytes. The challenge with pathogens and pathogen associated molecular patterns (PAMPs) also upregulated the mRNA levels of BmBr-C Z2 in hemocytes when compared with the control. By contrast, the ectopic expression of BmBr-C Z2 remarkably increased the production of antimicrobial peptides, while the knock-down of this gene by double stranded RNA decreased their production. Dual-luciferase assay exhibited that BmBr-C Z2 induced the expression of lysozyme by directly binding to its promoter region. The treatment of Escherichia coli following the knock-down of BmBr-C Z2 strongly reduced the survival rate of silkworm larvae. These results suggest that BmBr-C Z2 plays an important biological role in the innate immune responses of silkworm by regulating immune-related genes. Highlights: Both 20E and microbial administration increased the expression of BmBR-C Z2. BmBR-C Z2 regulated the expression of AMPs. BmBR-C Z2 enhanced lysozyme expression by binding to its promoter region. E. coli treatment after BmBR-C Z2 suppression reduced the silkworm survival.